Comparative study between single versus double burr-hole drainage of unilateral chronic subdural haematoma (Bangladesh Medical Journal, 2014)
Chronic subdural haematoma (CSDH) is defined as the haematoma in the subdural space which tend to occur in the elderly several weeks after head injury. The incidence of CSDH varied from 1.72 per 100,000 inhabitants per year in Finland to 13.1 per 100,000 inhabitants per year in Japan with a peak incidence in the sixth and seventh decade of life. CSDH is a common treatable cause of dementia. The principal techniques used in the treatment of CSDHs are presently burr hole, twist drill craniostomy, craniectomy and craniotomy. The aim of this study was to assess clinical outcome in unilateral chronic subdural haematoma psatients treated by single or double burr-hole drainage. This clinical trial was carried out at the department of neurosurgery, BSMMU from June 2010 to November 2011. A total of 40 consecutive patients with their age ranged from 50 to 70 years with GCS 9 to 13 & haematoma volume greater than 30cc were included in this study and randomly divided into two groups. In group A, patients with chronic subdural haematoma (CSDH) were managed with double burr-hole drainage. In group B, patients were managed with single burr-hole drainage. Clinical outcome was measured on the 1st post operative day, 3rd post operative day and at the time of discharge (usually on the 7th post operative day) and at 1 month follow-up by measuring Glassgow coma scale (GCS), improvement of limb weakness and Markwalder grading scale. In this study double burr-hole drainage and single burr-hole drainage surgery shows equal success in the management of CSDHs. DOI: http://dx.doi.org/10.3329/bmj.v43i1.21370 Bangladesh Med J. 2014 January; 43 (1): 13-16